Carta de Jorge Mañach a Roberto H. Todd - Mañach, Jorge; Todd, Roberto H. (My University, 1941)
Agradecimiento por la atenciones recibidas.
Keywords: Mañach, Jorge--Correspondence.; Mañach, Jorge--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.